Concurrent Cryptococcal Meningitis, Disseminated Histoplasmosis, and Tuberculosis Lymphadenitis in a Newly Diagnosed Human Immunodeficiency Virus Patient: An Unusual Case Report - Kadam, Pallavi; Swamy, V.H.T.; Areeparambil, Sudheer; Rao, Srirama; Madhan, Ramesh (Journal of Pharmacy Practice and Community Medicine, 2026)
A 45-year-old male with a recent diagnosis of Human Immunodeficiency Virus (HIV) infection, initiated on antiretroviral therapy one month earlier, presented with a 15-day history of persistent headache, accompanied by vomiting for three days, cough, and significant weight loss over the past month. Physical examination revealed palpable left cervical lymphadenopathy. The patient had previously been hospitalized at another center, where he received treatment; however, evaluation for histoplasmosis had not been performed at that time. Fine-Needle Aspiration Cytology (FNAC) of the cervical lymph node demonstrated granulomatous lymphadenitis with the presence of Histoplasma species, confirming disseminated histoplasmosis. Due to persistent neurological symptoms, Cerebrospinal Fluid (CSF) examination was performed. India ink staining revealed numerous Cryptococcus organisms, while CSF parameters showed a glucose level of 28 mg/dL and protein level of 174 mg/dL, findings consistent with cryptococcal meningitis. The patient was started on amphotericin B and fluconazole, along with Antitubercular Therapy (ATT), levetiracetam for seizure prophylaxis, and supportive care. During treatment, amphotericin B-associated nephrotoxicity developed, with serum creatinine rising to 1.45 mg/dL. Consequently, amphotericin B was discontinued, and antifungal therapy was modified to flucytosine while continuing fluconazole and ATT. Following adjustment of the treatment regimen and supportive management, the patient showed gradual clinical improvement. This case describes a rare coexistence of cryptococcal meningitis, disseminated histoplasmosis, and tuberculous lymphadenitis in a newly diagnosed HIV patient. The report highlights the importance of early screening for multiple opportunistic infections, thorough diagnostic evaluation, and careful management of drug toxicities to improve outcomes in immunocompromised individuals.
Keywords: Cryptococcal meningitis; Histoplasmosis; HIV; Opportunistic infections; Tuberculosis